Qualitative exploration of cultural factors influencing diet among African-, Caribbean- and US-born Blacks living in the northeast USA. (2019) - Brown, A. G. M.; Houser, R. F.; Mattei, J.; Lichtenstein, A. H.; Folta, S. C.
Abstract: Limited research considers the ethnic and cultural diversity among the US Black population, and how this diversity influences diet. The purpose of the present qualitative study is to (1) explore the influence of culture, nativity and ethnicity on the diet of US-born, African-born and Caribbean/Latin American-born Blacks and (2) explore a model of dietary acculturation among the African-born and Caribbean/Latin American-born Blacks. The purposive sample included twenty-two US-born, fifteen Caribbean/Latin American-born and ten African-born Blacks ( n 47) living in Boston, who participated in either an in-depth interview ( n 12) or a focus group (five groups, size 5–9). Satia-Abouta's model of dietary acculturation informed the interview and focus group questions, which explored the influence of psychosocial factors, taste preferences and environmental factors on dietary changes. NVivo 10 software was utilised for the coding and analysis. Topics based on a priori and posteriori analyses included differences in psychosocial factors and taste preferences and environmental factors by nativity. Caribbean/Latin American-born and African-born Blacks expressed the importance of cultural identity in their dietary preferences and found adaptive strategies to maintain cultural diet, while US-born Blacks demonstrated a variety of preferences for traditionally African American foods. Environmental factors varied by place of birth and residence, with US-born Blacks citing poorer quality and limited affordability of foods. These findings suggest the importance of psychosocial and environmental factors in shaping the diet of the ethnically diverse US Black population and underscore the dietary diversity within and across the different ethnic groups of Blacks.